Nova ocorrência de Heliotropium L. (Boraginaceae, Heliotropioideae) para o Sudeste do Brasil - Miranda de Melo, José Iranildo; Ranga, Neusa Taroda [UNESP] (Universidade Estadual de Maringa, 2003)
During the study of Heliotropium L. genus in the project Flora Fanerogâmica do Estado de São Paulo, it was verified that Heliotropium fruticosum L. presents a new geographical occurrence in Southeast of Brazil. Description, illustration and comments about relationships, distribution and phenology, as well as a summary of examined material are included in this paper.
New occurrence of Heliotropium L. (Boraginaceae, Heliotropioideae) in Southeast of Brazil
Keywords: Boraginaceae; Heliotropium; New occurrence; Southeast of Brazil; Taxonomy; Brazil; nonhuman; plant; taxonomy; tropics; Heliotropium fruticosum